Por uma Geografia de Diamantina-MG - Guilherme Fortes Drummond Chicarino Varajão (2015)
This work is essentially a geographical study of Diamantina-MG. It has an intensive research design comprising of a detailed description of a given reality. The ensemble of the work is fundamentally guided by an inductive approach, with the search for explanations for the studied phenomena. It seeks to establish connections between events, mechanisms and structures. The process of analysis and synthesis for a Geography of Diamantina - is reflected in the structure of the work, which is divided into six chapters. Different spatial syntheses were achieved that portrayed Diamantina at different scales (regional and local) and periods (past and present). The research involved the compilation of various sources such as books and academic works; among theses, dissertations and articles, in addition to primary sources such as travelers' reports and historical maps. Site and situation studies were performed, revealing that the Village of Tijuco developed due to a special combination of factors. The characterization of the towns site was done by field works which involved the collection of various data about the physical environment, such as predominant types of rocks and soils. Considering the characteristics of the Southern Espinhaço Range, the site was favorable to foster administrative and commercial functions. Diamantinas urban development has always been associated with the regional context in which it takes part. Inserted into the paths network, Diamantina was reference to distant urban centers but had its relative importance decreased, especially during the twentieth century. Focused on a local scale, the urban evolution of Diamantina was analyzed, through remote sensing techniques, with the use of aerial photographs and satellite images. It was found that throughout the twentieth century the city was modernized, especially in its central and pericentral areas, while the peripheral areas expanded with little or no planning. Currently, according to the study performed about its major urban functions, Diamantina has rare services that promote important external relationships, acting as an intermediary between the High Jequitinhonha Valley and the State capital. The morphologicfunctional zoning, based on the model of Amorim Filho (2007), was carried out by organizing the data collected in situ into a Geographic Information System. Special features of the of citys urban dynamics and structure came to light, though the zoning confirmed the middle-sized city position that Diamantina holds. Through unsystematic observations and 402 structured interviews, Diamantinas positively and negatively valued places by residents were studied. Thus, various relationships were observed between the collective preferences and the morphologic and functional characteristics of the city. In addition to the spatial perspective, the chapters are tangled due to the alternate or simultaneous employment of concepts and geographical principles. Thus, the connection between chapters (horizontal forces) and the exchanges with other areas of knowledge (vertical forces - centripetal and centrifugal) were guaranteed.